The Fuzzy Length of Fuzzy Bounded Operator - Kider, Jehad R.; Mousa , Jaafar Imran (Iraqi Journal of Science, 2022)
In this paper we recall the definition of fuzzy length space on a fuzzy set after that we recall basic definitions and properties of fuzzy length. We define fuzzy bounded operator as an introduction to defined fuzzy length of an operator then we proved that the fuzzy length space FB ̃ ̃ consisting of all fuzzy bounded linear operators from a fuzzy length space ̃ into a fuzzy length space ̃ is fuzzy complete if ̃ is fuzzy complete. Also we proved that every finite dimensional fuzzy length space is fuzzy complete.